2006
DOI: 10.1111/j.1540-8167.2006.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Individuals with the Brugada Electrocardiogram: A Meta‐Analysis

Abstract: Our findings suggest that a history of syncope or SCD, the presence of a spontaneous Type I Brugada ECG, and male gender predict a more malignant natural history. Our findings do not support the use of a family history of SCD, the presence of an SCN5A gene mutation, or EPS to guide the management of patients with a Brugada ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(249 citation statements)
references
References 75 publications
(91 reference statements)
10
219
3
7
Order By: Relevance
“…The PR prolongation could differentiate between SCN5A and non ‐SCN5A BrS patients 19, 20. The study herein also showed longer PR intervals in BrS patients with either R1193Q or H558R SCN5A polymorphisms (Tables 2, 3 through 4).…”
Section: Discussionsupporting
confidence: 57%
“…The PR prolongation could differentiate between SCN5A and non ‐SCN5A BrS patients 19, 20. The study herein also showed longer PR intervals in BrS patients with either R1193Q or H558R SCN5A polymorphisms (Tables 2, 3 through 4).…”
Section: Discussionsupporting
confidence: 57%
“…Recent meta-analysis, which included, in most of the studies, all BrS ECG patterns, revealed that worldwide BrS ECG patterns prevalence is 0.4% and it is 9 times higher in men than in women (0.9% vs. 0.1%) [13]. This result is consistent with other reports which indicate that the BrS occurrence may be even eight times higher in men than in women [6,14]. The trends in incidence of spontaneous type 1 BrS ECG pattern are changing.…”
Section: Epidemiologysupporting
confidence: 86%
“…Zespół Brugadów jest dziedziczony jako cecha dominująca i charakteryzuje się penetracją zależną od wieku i płci. Objawy kliniczne choroby są częstsze u osób dorosłych, a u mężczyzn występują 8-krotnie częściej niż u kobiet [450]. Częstoskurcz komorowy występuje w średnim wieku 41 ± 15 lat, ale może się ujawnić w dowolnym wieku, zwykle w spoczynku lub podczas snu [451].…”
Section: Definicje I Epidemiologiaunclassified